The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1038/sj.onc.1206402
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral agent Cidofovir decreases Epstein–Barr virus (EBV) oncoproteins and enhances the radiosensitivity in EBV-related malignancies

Abstract: The Epstein-Barr virus (EBV) is involved in the carcinogenesis of several human cancers such as nasopharyngeal carcinoma (NPC) and Burkitt lymphoma (BL). Given the consistent role of EBV in transformation and maintenance of malignant phenotype, antiviral strategies provide an attractive approach to target EBVexpressing cells. In that aim, we have tested the Cidofovir, which is an acyclic nucleoside phosphonate analog known to exert an antiproliferative activity in some human virusrelated tumors. Here, we show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 41 publications
0
32
1
Order By: Relevance
“…16 Widespread apoptosis was produced in all 3 types of tumors. Thus, the data suggest that apoptosis was dependent on neither p53 nor LMP1 expression in contrast to the results of Abdulkarim et al 16,38 We had also reported previously that PARP cleavage was induced by cidofovir in NPC-KT cells, which do not express LMP1. 17 Although LMP1 signaling might be partially involved, the main pathway of cidofovir-induced apoptosis may be LMP1-independent.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…16 Widespread apoptosis was produced in all 3 types of tumors. Thus, the data suggest that apoptosis was dependent on neither p53 nor LMP1 expression in contrast to the results of Abdulkarim et al 16,38 We had also reported previously that PARP cleavage was induced by cidofovir in NPC-KT cells, which do not express LMP1. 17 Although LMP1 signaling might be partially involved, the main pathway of cidofovir-induced apoptosis may be LMP1-independent.…”
Section: Discussioncontrasting
confidence: 55%
“…Abdulkarim et al 38 showed that cidofovir induced a downregulation of the EBV oncoprotein latent membrane protein-1 (LMP1) associated with a decrease of the antiapoptotic Bcl-2 and an increase of the proapoptotic Bax protein in NPC C15. 38 Previously, we showed that local or systemic administration of cidofovir produced striking effects on growth of LMP1-expressing NPC C15 xenografts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests a promising nontoxic and effective therapy for EBV-positive lymphoproliferative diseases. Abdulkarim et al (2003) also demonstrated that treatment with Cidofovir combined with ionizing radiation leads to tumor remission without increasing toxicity in EBV-positive cells (Raji and C15) in nude mice. This approach is likely to greatly improve conventional cancer therapies.…”
Section: Drugs Targeting Bcl Family Members In Ebv-associated Diseasesmentioning
confidence: 99%
“…28 Abdulkarim et al 29 reported that antiviral agent Cidofovir could downregulate the EBV oncoprotein LMP1 expression, which was associated with a decrease in antiapoptotic Bcl-2 protein and an increase of the proapoptotic Bax protein in Raji (BL) and C15 (NPC) cells. However, the mechanism of Codofovir's effect on the LMP1 and bcl-2 protein expression was not defined.…”
Section: Inhibition Of Bcl-2 Protein Expression and Induced Apoptosismentioning
confidence: 99%